Sonic and Photonic Crystals - Chen, Lien-Wen; Yeh, Jia-Yi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sonic/phononic crystals termed acoustic/sonic band gap media are elastic analogues of photonic crystals and have also recently received renewed attention in many acoustic applications. Photonic crystals have a periodic dielectric modulation with a spatial scale on the order of the optical wavelength. The design and optimization of photonic crystals can be utilized in many applications by combining factors related to the combinations of intermixing materials, lattice symmetry, lattice constant, filling factor, shape of the scattering object, and thickness of a structural layer. Through the publications and discussions of the research on sonic/phononic crystals, researchers can obtain effective and valuable results and improve their future development in related fields. Devices based on these crystals can be utilized in mechanical and physical applications and can also be designed for novel applications as based on the investigations in this Special Issue.